Pengembangan : Media Berhitung Berbantuan Spinning Wheel Number untuk Meningkatkan Minat Belajar - Muthi'ah Muthmainna; Muhammad Guntur; Nilam Permatasari (Institut Agama Islam Hidayatullah Batam, 2026)
This research was motivated by students' low interest in learning mathematics, particularly in the topic of repeated addition among third-grade students at SDN 60 Salubattang. The purpose of this study was to determine the results of the needs analysis for media development, as well as the validity, practicality, and effectiveness of a counting learning media assisted by a Spinning Wheel Number on repeated addition material. This study employed the Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects consisted of one teacher and 18 third-grade students of SDN 60 Salubattang. Data were collected through interviews, questionnaires, documentation, and tests. The results showed that the media achieved a validity score of 83.33% from the media expert and 100% from the material expert, both categorized as very valid. The practicality assessment obtained scores of 96% from students and 95% from the teacher, indicating that the media was very practical. The effectiveness test resulted in an N-Gain score of 0.58, which falls into the moderately effective category. The implications of this study are that teachers can utilize the Spinning Wheel Number media as an innovative instructional medium in mathematics learning to help students understand the concept of repeated addition in a more concrete way. This media can serve as an engaging and interactive learning alternative to increase the learning interest of third-grade students at State Elementary School 60 Salubattang. Thus, the Spinning Wheel Number media is appropriate for use in mathematics learning on the topic of repeated addition.